Barriers to high school and university students' physical activity: A systematic review protocol. (2021) - Ferreira Silva, Regina Márcia; Mendonça, Carolina Rodrigues; Noll, Matias
Highlights: high physical inactivity among adolescents and adults. physical inactivity as a public health problem. barriers to physical activity among students. Abstract: Physical inactivity is a prevalent issue affecting both adolescents and adults, and the factors that negatively influence engagement in physical activities are called barriers. The importance of physical activities for health and the impact of health on the learning process make it necessary to identify these barriers. Studies that identified barriers to physical activity among high school and university students will be searched in electronic databases (CINAHL, Cochrane Library, Embase, PubMed, and Scopus) with no time-period restrictions. The evaluation of the evidence on the barriers to physical activity for students, will be contribute to public interventions aimed at improving health and quality of life, as well as reducing health costs. Systematic review registration: PROSPERO CRD42020198899.